PENGARUH MIND MAPPING DALAM MENINGKATKAN DAYA INGAT SISWA - Hutagaol, Artha Taruji Borneo (IAIN Pontianak, 2023)
This research aims to analyze the use of mind mapping method in enhancing students' memory. This study falls under qualitative research, specifically the category of library research. Library research is a study that utilizes theoretical studies to gather information and data by utilizing various sources available in the library such as books, journals, news, etc. Data is collected through documentation techniques, which involve reading, studying, and noting relevant literature related to learning. The use of mind mapping in improving learning outcomes is chosen by teachers as one of the alternatives. According to Drever (in Walgito, 2004), memory is one of the characteristics possessed by living beings. Useful experiences that we forget can affect behavior and future experiences. Memory not only involves recall and recognition but also involves the process of bringing back memories. According to Tulving, memory is the way in which individuals can retain and retrieve past experiences for use in the present (Sternberg, 2006). Therefore, it can be concluded that memory is an individual's ability to store, process, and recall experiences, data, and information acquired in the past for future use, considering the situation and conditions. Mind Mapping is a learning method designed to help students determine and organize the core of the readings. Therefore, the implementation of the Mind Mapping model can enhance students' memory.